Metal oxides inside carbon nanoreactors for environmental remediation - Astle, Maxwell Andrew (2019)
The work presented in this thesis demonstrates the key principles of ‘catalytic nanoreactors’ and ‘nanosponges’, whereby the unique effects of spatial confinement inside carbon nanotubes can be harnessed to drive important decontamination reactions. The versatile gas and liquid phase filling strategies developed, allow control over the structure and functionality of the encapsulated metal oxide by varying the synthesis conditions or by post-synthesis thermal treatment. Using a holistic approach, a diverse range of bulk and local probe characterisation techniques were applied and a strategy for the characterisation of these challenging nanomaterials established. Group IV (Ti, Zr and Hf) nanomaterials are found to coat the interior channel of hollow graphitised carbon nanofibres (GNF). This amorphous structure with a thickness of 6-10 nm provides maximised catalytic surface area and minimal transport resistance for reactants. Discrete group VI (Cr, Mo and W) metal oxide nanomaterials are embedded within GNF and effectively catalyse the combustion of the GNF due to the interactions between the guest and host species. As a result of spatial confinement, a catalytic carbon nanoreactor containing hydroxylated zirconia thin films (ZrOx(OH)y@GNF) promoted a four-fold enhancement in the rate of hydrolysis of organophosphorus compounds relative to the GNF and hydroxylated zirconia in isolation. Confined molybdenum dioxide nanoparticles inside carbon nanoreactors also showed superior abilities towards oxidative desulphurisation affording over 98 % fuel desulphurisation at low catalyst loading. The roles of the carbon nanoreactors were found to improve the activity and stability of catalytic centres in these reactions as well as enhancing the local concentration of reagents to catalysts. Surprisingly, the nanotube cavity was found to sequester the undesirable species out of the reaction media allowing them to act as a nanosponge. This effect provided further enrichment of the molecules within the nanoreactor and also an effective adsorption mechanism increasing the removal of the toxic species. This synergistic dual functionality has led to the improved catalytic performance and demonstrated amplified nanoremediation applicable to nerve agent destruction and the production of ultra-low sulphur fuel.